Job Satisfaction Mediating Organizational Climate, Transformational Leadership, Need for Achievement, on Employee Performance in the Production Division of the Automotive Industry - Hutabarat, Rinsan; Yusnita, Nancy; Sunaryo , Widodo (Jurnal Locus Penelitian dan Pengabdian, 2025)
In a highly competitive automotive industry, productivity and efficiency are highly dependent on employee performance, especially at the level of production parts operators. The purpose of this study is to test and analyze the direct and indirect influence of organizational climate, transformational leadership, need for achievement and job satisfaction on employee performance in the Automotive Industry in Karawang Regency. This study uses a quantitative research method. Data analysis uses path analysis. The results of the study show that the organizational climate, transformational leadership, and need for achievement have a direct positive and significant influence on employee performance and job satisfaction. In addition, job satisfaction has also been proven to have a positive effect on employee performance. This study also reveals that job satisfaction plays a significant mediator in the relationship between organizational climate, transformational leadership, and  the need for achievement on employee performance, both directly and indirectly. Thus, strengthening these three factors and increasing overall job satisfaction can effectively encourage employee performance improvement.